Indonesia’s Dilemma In Addressing Rohingya Refugee Crisis - Thoriq Azraqi; Yandry Kurniawan (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: National resilience is understood as a state's ability to maintain political, social, economic, and security stability in the face of internal and external pressures in a sustainable manner. The purpose of this paper is to analyse Indonesia's policy dilemma in handling the Rohingya refugee crisis by positioning it at the intersection of humanitarian obligations, national interests, and regional stability. The research focuses on how Indonesia responds to international normative pressures as well as the domestic dynamics that influence refugee governance. Study Design/Methodology/Approach: A qualitative methodology was adopted using a systematic literature review of 28 appropriate academic articles. The literature was reviewed using a taxonomic technique to cluster around key themes, namely, the respect for human rights and the non-refoulement principle; the domestic social and political context; and the policy responses of government and international actors in relation to the Rohingya refugee crisis. Findings: The findings suggest that Indonesia is structurally trapped in an awkward position of humanitarian commitment and limited institutional capacity and national legal framework. Indonesia has signed the 1951 Refugee Convention but has not yet acceded to it and is still using the humanitarian consideration approach. However, domestic social, economic, and political pressures, as well as weak regional coordination, limit the effectiveness of implemented policies. Originality/Value: This research contribution offers an analytical mapping of Indonesia's position in the Rohingya refugee crisis from a policy and national resilience perspective. The research findings reinforce the importance of a collaborative and sustainable approach to maintaining a balance between humanitarian values and national stability.